2015
DOI: 10.7882/az.2015.014
|View full text |Cite
|
Sign up to set email alerts
|

The Red-whiskered Bulbul Pycnonotus jocosus in Australia – a global perspective, history of introduction, current status and potential impacts

Abstract: The Red-whiskered Bulbul Pycnonotus jocosus naturally occurs from the Indian subcontinent to the northern Malay Peninsula. Its anthropogenic spread also encompasses Australia, Japan, the southern Malay Peninsula, Singapore, Florida, California, 11 islands in the Indian Ocean, and Oahu, Hawaii. The earliest known introduction occurred in Sydney in 1865, with subsequent releases in the 1900's leading to establishment. It was first released in Melbourne, Victoria in 1915, with a population establishing in the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The country's terrestrial vegetation types can be broadly grouped into nine biomes that range from deserts and Mediterraneanclimate shrublands (fynbos) in the west to grasslands and savanna in the eastern interior, and evergreen forests in high rainfall areas along the east coast (Mucina and Rutherford 2006). Three areas within these biomes-the Cape Floristic Region, the Succulent Karoo, and the Maputaland-Pondoland-Albany region-have been designated global biodiversity hotspots (Myers et al 2000;Mittermeier et al 2004). The marine realm includes several ecosystems in the surrounding Indian and Atlantic oceans and offshore islands (van Wilgen et al 2020a, Chap.…”
Section: Introductionmentioning
confidence: 99%
“…The country's terrestrial vegetation types can be broadly grouped into nine biomes that range from deserts and Mediterraneanclimate shrublands (fynbos) in the west to grasslands and savanna in the eastern interior, and evergreen forests in high rainfall areas along the east coast (Mucina and Rutherford 2006). Three areas within these biomes-the Cape Floristic Region, the Succulent Karoo, and the Maputaland-Pondoland-Albany region-have been designated global biodiversity hotspots (Myers et al 2000;Mittermeier et al 2004). The marine realm includes several ecosystems in the surrounding Indian and Atlantic oceans and offshore islands (van Wilgen et al 2020a, Chap.…”
Section: Introductionmentioning
confidence: 99%
“…They are therefore conspicuous and easy to detect, and the red-whiskered bulbul is no exception. In studies about this species as an invader, its presence is usually identified by sightings or by their song (Carleton and Owre, 1975;Mandon-Dalger et al, 1999;Mo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known to venture into areas of native vegetation, and can even establish in these areas. This behaviour has been observed both on islands such as Réunion and Mauritius, and in continents, such as Australia (Mandon-Dalger et al, 1999;Linnebjerg et al, 2009Linnebjerg et al, , 2010Mo, 2015). It seems to prefer lowlands and areas with plentiful resources due to alien plant species (Forys and Allen, 1999;Mandon-Dalger et al, 1999;Clergeau and Mandon-Dalger, 2001;Linnebjerg et al, 2009Linnebjerg et al, , 2010.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations